Turning Our Gaze to Prosocial Media Effects: What is and isn’t Known - Prot, Sara; Gentile, Douglas (Empirical Musicology Review, 2015)
Clark and Giacomantonio (2015) raise several valuable research questions concerning the relationship between empathy and music genre preferences, and present interesting exploratory analyses concerning this issue. This response provides a review of findings from similar past studies in this area and draws out some of the themes that can help the field progress. An overview is given of established effects of prosocial media use on prosocial behavior in real life as well as past findings concerning empathy as a mediator of these effects. Several key research questions that remain to be explored are also considered (such as a need for research concerning potential mediators and moderators of prosocial media effects).